Comparison of the Effectiveness of Time Perspective and Emotional Efficacy-Based Interventions on Social-Emotional Loneliness and Self-Concealment in Single Women in the Climacteric Period - Mohammadi , Fatemeh Sadat; Hashemi, Masoumeh; Ghahremani Ochghaz , Maryam (Psychology of Woman Journal, 2026)
Objective: This study aimed to compare the effectiveness of Time Perspective Therapy (TPT) and Emotional Efficacy Therapy (EET) on social-emotional loneliness and self-concealment among single women in the climacteric period.Methods and Materials: This study employed a quasi-experimental, pre-test, post-test, and follow-up design with a control group. The statistical population consisted of single women navigating the climacteric phase. Participants were selected through purposive sampling and randomly assigned to one of three groups: Time Perspective Therapy, Emotional Efficacy Therapy, or a waitlist Control group. Data were collected using standardized self-report inventories measuring social-emotional loneliness (including romantic, family, and social subscales) and self-concealment. Data analysis was conducted using repeated measures ANOVA and Bonferroni post-hoc tests to evaluate the main effects and interactions across the three assessment phases.Findings: The repeated measures ANOVA demonstrated significant main effects of time and time group interactions for total social-emotional loneliness, romantic loneliness, family loneliness, social loneliness, and total self-concealment (all ). Bonferroni post-hoc analyses revealed that both TPT and EET significantly improved all measured outcomes across the post-test and follow-up phases compared to the control group. Crucially, the comparative analysis showed that TPT was significantly more effective than EET in reducing total social-emotional loneliness, romantic loneliness, social loneliness, and total self-concealment (all ). The only exception was family loneliness, where no statistically significant difference was observed between the TPT and EET groups ( ).Conclusion: While both therapeutic modalities successfully alleviate psychological distress, Time Perspective Therapy is generally superior to Emotional Efficacy Therapy in reducing loneliness and self-concealment among single women in the climacteric period.